Organizational ethnography studying the complexities of everyday life - Ybema, Sierk 1967-; Yanow, Dvora; Wels, Harry; Kamsteeg, Frans (SAGE, 2009)
"Organizational Ethnography brings contributions from leading scholars in organizational studies that help to develop an ethnographic perspective on organizations and organizational research. The authors explore the special problems faced by organizational ethnographers, from questions of gaining access to research sites to various styles of writing ethnography, the role of friendship relations in the field, ethical issues, and standards for evaluating ethnographic work."--Publisher's description.